Growth of F1 and F2 calf Kiwi Cross x Holstein - Felipe Nieto-Sierra, David; Andres Timaran-Rivera, Edmundo; Carlos Montes-Vergara, Jose; Castro-Rincon, Edwin; David Mogollon-Garcia, Henry [UNESP] (Univ Costa Rica, 2021)
Introduction. In the dairy cattle production cycle, the calf growth time represents a period of expenses and little return for the producer, however, the preparation of healthy females during this period is essential to incorporate productive females into the herd that guarantee the financial return. Objective. To determine the productive and bovinometric parameters of the subsidiaries one (F1) and two (F2) resulting from the cross between the Kiwi Cross x Holstein breeds. Materials and methods. This work was carried out at the Obonuco Research Center of the Colombian Corporation for Agricultural Research (AGROSAVIA), located in Pasto, Narifio, Colombia. Twenty F1 (1/2 Kiwi Cross -1/2 Holstein-Friesian) and twenty F2 (3/4 Kiwi Cross - 1/4 Holstein-Friesian) calves were used. Production and bovinometric variables were registered during the first and seventh month of age. Results. F1 calves in the third month showed greater weight compared to the F2 (158.9 +/- 2.5 vs. 115 +/- 2.5 kg, respectively). Both generations showed a decrease in daily weight gain between the third and seventh month of age. In the seventh month, the F1 calves showed higher values compared to the F2 in the variables perimeter of the thorax (126.5 +/- 1.0 cm vs 116.9 +/- 0.9 cm), height at the cross (102.4 +/- 0.7 cm vs 97.0 +/- 0.7 cm), height at the haunch (107.3 +/- 0.7 vs 101.2 +/- 0.7 cm), distance between ileum and ischium (34.5 +/- 0, 4 vs 32.3 +/- 0.4 cm) and distance between sitting bones (11.2 +/- 0.1 vs. 10.2 +/- 0.1 cm). Conclusion. Between the third and seventh month of age, the main differences between the two subsidiaries were observed in most of the variables, as the percentage of Kiwi Cross increased, animals of smaller size and weight were obtained.
Keywords: crossing; dairy cattle; daily gain; bovinometric measurements; weight